2018
DOI: 10.4014/jmb.1807.07008
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing astaxanthin accumulation in Haematococcus pluvialis by coupled light intensity and nitrogen starvation in column photobioreactors

Abstract: Natural astaxanthin mainly derives from a microalgae producer, Haematococcus pluvialis. The induction of nitrogen starvation and high light intensity is particularly significant for boosting astaxanthin production. However, the different responses to light intensity and nitrogen starvation needed to be analyzed for biomass growth and astaxanthin accumulation. The results showed that the highest level of astaxanthin production was achieved in nitrogen starvation, and was 1.64 times higher than the control group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 38 publications
8
31
0
Order By: Relevance
“…Our results also revealed that (1) T-AST and T-TAG contents signi cantly increased under HL-W, HL-B, 1/4N, HL-W+1/4N, and HL-B+1/4N conditions, respectively, which was consistent with previous study [34,41], (2) M-AST was the main form which is also proven by previous studies [36][37][38][39], (3) compared to ND stress, HL was more effective in inducing AST accumulation especially under the blue HL condition, which has been testi ed in our previous study [50], (4) coupled HL and ND dual stimulation might be better choices in improving AST and TAG accumulation in H. lacustris ( Fig. 1) [53]. Zhang et al (2018) indicated that HL intensity synergizes with ND can effectively stimulate the biosynthesis of AST [53].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our results also revealed that (1) T-AST and T-TAG contents signi cantly increased under HL-W, HL-B, 1/4N, HL-W+1/4N, and HL-B+1/4N conditions, respectively, which was consistent with previous study [34,41], (2) M-AST was the main form which is also proven by previous studies [36][37][38][39], (3) compared to ND stress, HL was more effective in inducing AST accumulation especially under the blue HL condition, which has been testi ed in our previous study [50], (4) coupled HL and ND dual stimulation might be better choices in improving AST and TAG accumulation in H. lacustris ( Fig. 1) [53]. Zhang et al (2018) indicated that HL intensity synergizes with ND can effectively stimulate the biosynthesis of AST [53].…”
Section: Discussionsupporting
confidence: 92%
“…1) [53]. Zhang et al (2018) indicated that HL intensity synergizes with ND can effectively stimulate the biosynthesis of AST [53]. The previous studies have indicated that AST is predominantly esteri ed with FAs and three forms of AST are present, and the main form of AST is EAST (MAST, 70% and DAST, 25%), which is stored in TAG-rich cytosolic oil bodies (OBs) in H. lacustris [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The natural astaxanthin mainly derives from the microalgae producer, Haematococcus. The induction of nitrogen starvation and high light intensity is particularly significant for boosting astaxanthin production [51].…”
Section: The Differential Expression Patterns and The Complementary Rmentioning
confidence: 99%